Effect of visible presence of policing activities on drivers' vigilance and intention to refrain from non-driving activities: A scenario-based survey of general Japanese drivers. (December 2019) - Nakano, Yukako; Okamura, Kazuko; Kosuge, Ritsu; Kihira, Makoto; Fujita, Goro
Highlights: Evaluates the effect of the visible policing activities aimed at motivating drivers to refrain from non-driving activities. Assessed drivers' self-reported vigilance and intention to refrain from non-driving activities on hypothetical scenarios. Drivers' intentions were higher when they saw the policing activities compared with the other road safety interventions. Drivers' intentions were higher when they saw a police officer compared with a police car. Drivers' intentions were enhanced by increasing conspicuousness of the policing activities. Abstract: Driver distraction is an important issue for road safety. The visible presence of policing activities alongside roadways seems to be significant in preventing driver distraction and other unsafe driving behaviors. The purpose of this study was to provide evidence of the effectiveness of visible policing presence on drivers' self-reported intention to refrain from non-driving activities and that this effectiveness can be enhanced by manipulating deployment even with limited resources. We conducted a scenario-based survey to compare drivers' self-reported intention to refrain from non-driving activities and their vigilance state across several hypothetical driving situations. The three aims of the study were to examine whether drivers' self-reported vigilance and intention to refrain from non-driving activities were associated with (a) the presence or absence of common forms of roadside policing, (b) the agent (police vs. civilian) and medium (human vs. advertisement) of road safety interventions, and (c) different forms of policing (police officer vs. police car) and their respective levels of conspicuousness. Japanese drivers ( N = 367) were randomly assigned to receive one of three booklets that included a scenario-based survey. The three booklets contained different combinations of various hypothetical driving scenarios based on the three experiment designs (a, b, c) described above. Participants were asked to rate their vigilance and their intention to refrain from non-driving activities in hypothetical driving situations that varied by the presence or absence of policing and how conspicuous that presence was. We conducted repeated measures within-subject analysis of variance using the three experimental designs. The results showed that the presence of a single police unit engaged in policing activities was associated with more vigilance and greater intention to refrain from non-driving activities. The results suggested that effectiveness of visible policing could be enhanced by increasing conspicuousness of police officers in order to help drivers more easily recognize the presence of police without having to purchase extra equipment. These findings provide useful insights for traffic police to conduct routine policing practices more efficiently to address non-driving activities. Future research is needed to examine these results in a real-world setting.